Determinants of Successful Vaginal Birth After Cesarean Section: A Retrospective Cohort Study in Southeast China - Xiu YL; Lv BQ (International Journal of Women's Health)
Ying-Ling Xiu, Bing-Qing Lv Department of Gynecology and Obstetrics, Fujian Maternal and Child Health Hospital, Fuzhou, Fujian Province, 350000, People’s Republic of ChinaCorrespondence: Bing-Qing Lv, Department of Gynecology and Obstetrics, Fujian Maternal and Child Health Hospital, No. 18 of Daoshan Road, Gulou District, Fuzhou, Fujian Province, 350000, People’s Republic of China, Tel +86 18950330039, Email Lvbingqing2024@163.comObjective: This study aimed to identify factors influencing the success of a trial of labor after cesarean section (TOLAC) and to evaluate associated maternal and neonatal outcomes.Methods: A retrospective analysis was conducted on data from women with a prior cesarean section who underwent TOLAC at Fujian Maternity and Child Health Hospital in Southeast China between January 2016 and January 2018. Of the 1179 women who attempted TOLAC, 1038 achieved vaginal birth after cesarean (VBAC) while 141 experienced unsuccessful trials. Sociodemographic and clinical characteristics were compared between the successful and unsuccessful TOLAC groups using the t-test for normally distributed data, non-parametric tests for non-normally distributed data, and the χ 2 test, corrected chi-square test, or Fisher’s exact test for categorical variables, as appropriate. Logistic regression analysis was performed to identify factors independently associated with successful TOLAC, with the results expressed as Odds Ratios (ORs) and corresponding 95% Confidence Intervals (CIs).Results: Multivariable logistic regression analysis revealed that maternal height (OR = 1.09, 95% CI = 1.05– 1.14), abdominal circumference (OR = 0.95, 95% CI = 0.91– 0.98), ultrasound-estimated fetal weight (OR = 0.99, 95% CI = 0.99– 1.00), and history of vaginal delivery (OR = 9.62, 95% CI = 2.33– 39.67) were independently associated with successful TOLAC. No significant differences were observed between the successful and unsuccessful TOLAC groups in terms of neonatal asphyxia, postpartum hemorrhage, placental abruption, or bladder injury.Conclusion: Maternal height, abdominal circumference, ultrasound-estimated fetal weight, and history of vaginal delivery were identified as influential factors for VBAC success. Clinical evaluation of these factors may enhance the selection criteria for TOLAC candidates, potentially increasing VBAC rates and reducing cesarean section rates overall.Keywords: pregnancy outcome, prior cesarean delivery, trial of labor after caesarean section, vaginal birth after caesarean section